Organic fades analysis of romualdo formation (santana group, lower cretaceous from araripe basin): Characterization of sedimentary organic matter andpaleoenvironmental interpretation - Teixeira, Mari'lia Carvalho; Filho, Joao Graciano Mendoruja; De Oliveira, Antonio Donizeti; Assine, Mario Luis [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2018)
The paleoenvironmental reconstruction of the Santana Group (Late Aptian-Early Albian) is a matter of controversy, es pecially concerning the marine influence on sedimentation. In this context, palynofacies analysis can be applied as an important tool for characterization of depositional systems, through the determination of palynofacies and organic and geo- chemical parameters, based on the concentration and distribution of the organic matter components. Microscopy techniques in transmitted white light and blue/ultraviolet incident (fluorescence) and geochemical methods were used for the identi fication of the different groups and subgroups of the particulate organic matter in 58 samples from a sedimentary section of Romualdo Formation (Santana Group. Lower Cretaceous from Araripe Basin). Two distinct assemblies of particulate organic compounds events were identified. The first one is characterized by dominance of amorphous organic matter derived from plant tissues with high amounts of marine origin components. The second assembly is characterized by dominance from phytoclast group, showing high abundance of non-opaque non-bioestrutured phytoclasts. The studied lithologic profile was subdivided into five strati- graphic interv als. This feature allowed the verification of a cyclical pattern in the organic material supply in relation to relative sea level variations. In these stratigraphic intervals, at least two marine ingressions were recognized during the Romualdo Formation deposition. The first one marks the establishment of relatively stable deposition of the organic material, comprising intermediate-distal facies of an epicontinental sea environment. The second marine ingression is recorded by sedimentary7 organic matter deposited in proximal condi-tions with high influence of marine-derived components, suggesting deposition in nearshore to coastal settings.
Faciologia organica da formagao romualdo (grupo santana, cretaceo inferior da bacia do araripe): caracterizacao da materia organica sedimentar e interpretacao paleoambiental
Keywords: Araripe basin; Palynofacies: paleoenvironment; Romualdo formation; Sedimentary organic matter